INCREASE IN BRADYKININ LEVELS IN CHILDREN WITH OBSTRUCTIVE SYNDROME AND ITS CLINICAL SIGNIFICANCE (International journal of medical sciences, 2025)
This study examines changes in bradykinin levels and their clinical relevance in children with obstructive bronchitis who remain afebrile yet continue to exhibit bronchial obstruction and wheezing. Thirteen children aged 9 months to 3 years (8 girls, 5 boys) were evaluated. Despite normal ESR and CRP values, obstructive symptoms persisted. Bradykinin levels, measured by ELISA, were 2–3 times above the normal range (56.5–75.6 pg/mL). These findings highlight the pathogenic role of bradykinin in pediatric obstructive bronchitis and support its potential use as a diagnostic biochemical marker. Inhaled budesonide demonstrated noticeable clinical improvement, further implicating the kallikrein–kinin system in symptom persistence.